1980
DOI: 10.1902/jop.1980.51.3.167
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Localized Gingival Recessions: Part IV. Results After Three Years

Abstract: Twenty-six localized recessions treated with either a lateral sliding flap or a coronally repositioned flap procedure more than 3 years ago were reevaluated. Biometric measurements on the recipient and the donor of control teeth included: a) cementoenamel junction, gingival margin; b) sulcus depth; c) gingival margin, mucogingival line. These recordings were statistically compared to those taken 180 days after the surgical procedures were performed. Pairwise t tests were used to determine whether there were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
2
4

Year Published

1986
1986
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 8 publications
(3 reference statements)
4
45
2
4
Order By: Relevance
“…When more than one study reported follow-up data on the same patients, 45,46,65,69,70 we reported the data extracted from the most recent study; in one study, 65 we chose the shorter follow-up because it covered a larger number of patients.…”
Section: Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…When more than one study reported follow-up data on the same patients, 45,46,65,69,70 we reported the data extracted from the most recent study; in one study, 65 we chose the shorter follow-up because it covered a larger number of patients.…”
Section: Data Collectionmentioning
confidence: 99%
“…Trombelli et al 57 (CAF+TRC+FG/CAF+TRC) Pini-Prato et al 59 (CAF+Pol/CAF+RP) Pini-Prato et al 61 (CAF+FTens/CAF no FTens) CTG Bouchard et al 25 (CTG+TRC/CTG+CARC) Borghetti and Louise 24 (CTG+DPF/no treatment) Bouchard et al 32 (CTG+TRC/CTG+CARC) Harris 31 (FGG knife method/FGG parallel incision methods) Harris 43 (CTG/acellular dermal matrix) GTR Trombelli et al 77 (ePTFE/ePTFE+TRC+FG) Roccuzzo et al 78 Guinard and Caffesse 45 Caffesse and Guinard 65 Caffesse and Guinard 46 Kunjamma et al 8 Laney et al 14 Ricci et al 28 Harris 29 Zucchelli et al 33 Jepsen et al 34 Trombelli et al 37 Harris 38 Borghetti et al 40 Tatakis and Trombelli 41 Rosetti et al 42 Trombelli et al 58 Amarante et al 62 Sbordone et al 10 Daniel and Cheru 12 Jahnke et al 15 Paolantonio et al 17 1. If the reporting of probing depth (PD) before and after treatment is included, only 59 out of 90 articles (65.6%) would have been accepted.…”
Section: Cafmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Coronally positioned flaps were compared with lateral sliding flaps in the treatment of localized gingival recessions. 18,19 In a 6-month report, both techniques rendered satisfactory results, and no differences in tissue coverage, sulcus depth, or gain of attached gingiva were reported. An average of 2.7 mm of soft tissue coverage was obtained, with average recession coverage of 67%.…”
Section: Pedicle Graftsmentioning
confidence: 98%
“…25,26 With these procedures there is a risk of donor site recession particularly with the laterally repositioned flap of approximately 1 mm. 27 The mean root coverage achieved with a single stage coronally repositioned flap varies between 55-99% and complete root coverage ranges from 24-95% of sites. 25,26 Pini-Patro et al 28 concluded that in order to achieve 100% root coverage with a coronally repositioned flap, the flap should be over compensated by 2-2.5 mm and sutured tension free.…”
Section: Prognosismentioning
confidence: 99%